Analysis of Markers of Bone Remodeling and Systemic Lupus Erythematosus Activity Index Interconnections - Tsyhanyk L.; Abrahamovych O.; Abrahamovych U.; Romanyuk O.; Guta S. (Львівський клінічний вісник)
Introduction. Systemic Lupus Erythematosus (SLE) is an autoimmune systemic disease, which is characterized by multiple organ disorders, in particular – bones. The development of osteoporosis (OP) is an extended process and even the complicated aggravation does not have enough «instant» effect, which could be marked on the bone state and could have been tested via densitometry. Therefore, there is a necessity for research of much more important indicators. It became at once a peculiar marker of SLE activity and OP necessity. Aim. To analyze the interconnections between bone remodeling markers and Systemic Lupus Erythematosus activity index.